2010
DOI: 10.3802/jgo.2010.21.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of laparoscopic surgical staging-guided radiation therapy in locally advanced cervical cancer

Abstract: Objective: This study was designed to evaluate the survival benefit of laparoscopic surgical staging (LSS)-guided tailored radiation therapy (RT) in locally advanced cervical cancer (LACC). Methods: We retrospectively reviewed 89 LACC patients' medical records who primarily received non-surgical treatment, of which pretreatment LSS was performed in 20 (LSS group) and primary chemoradiation therapy (CCRT) without LSS (CCRT group) was carried out in 69 from January 2000 to January 2006. We analyzed clinical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Other limitations of this study include the assumption that there was no delay in the administration of definite CRT after nodal staging surgery. A major drawback of nodal staging surgery is the resultant delay in starting curative treatment, attributable to either an overburdened surgical schedule or postoperative morbidity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations of this study include the assumption that there was no delay in the administration of definite CRT after nodal staging surgery. A major drawback of nodal staging surgery is the resultant delay in starting curative treatment, attributable to either an overburdened surgical schedule or postoperative morbidity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Nevertheless, a number of studies have shown that, as observed in our study, lymphadenectomy-tailored RT does not seem to provide a benefit on survival in patients with LACC. 4,36 Some studies have shown a minimal therapeutic benefit for surgical LN removal by itself in women with LACC and positive LNs. 7,22,23,37 However, the only prospective randomized study comparing surgical and clinical staging showed a significantly worse outcome for patients who underwent surgical staging owing to a higher complication rate in this group, without any benefit associated to the resection of the metastatic LNs.…”
Section: Commentmentioning
confidence: 99%